Antibacterial therapy of sepsis in extracorporeal detoxication: current problems and ways to solve them - A. V. Marukhov; M. V. Zakharov; N. V. Chubchenko; A. N. Belskikh; L. V. Buryakova; D. Yu. Lazarenko (Вестник анестезиологии и реаниматологии, 2020)
The effectiveness of antibacterial therapy is a critical factor to improve treatment outcomes in sepsis patients. Impaired renal function and renal replacement therapy lead to a significant change in the pharmacokinetic parameters of most intravenous antibacterial drugs, which in many cases is accompanied by insufficient or excessive concentration in the blood which results in antibacterial therapy failure. The article presents current views and describes the current problems of antibacterial therapy for sepsis during the use of extracorporeal detoxification methods.The objective: to analyze publications on antibacterial therapy of sepsis during the extracorporeal detoxification.Results: the most accessible and effective method for solving the problem of inadequate dosage of antibiotics when using extracorporeal detoxification is to develop local protocols based on the results of pharmacokinetic studies.